Religiusitas, Persepsi Korupsi Pajak Pelayanan Fiskus dan Kepatuhan Wajib Pajak - Mahasurya, I Gst Ngurah Agastya; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p01, 2020)
This study aims to examine the effect of religiosity, perceptions of tax corruption, and the tax authorities on individual taxpayer compliance. This research was conducted at the Tabanan Primary Tax Service Office in Bali. The data analysis method used is multiple linear regression. The sample in this study was WPOP registered at Tabanan Primary Tax Office with 100 respondents. The method of determining the sample using convenience sampling, and data collected using a questionnaire. Based on the results of the study showed that religiosity, perceptions of tax corruption, and fiscal services affect the compliance of individual taxpayers in the Tabanan Primary Tax Office. This shows that religiosity, perceptions of tax corruption, and fiscal services can help taxpayers to carry out their tax compliance obligations. Keywords: Religiosity; Perception of Tax Corruption; Fiscus Services; Personal Taxpayer Compliance.